Genetic Diversity of the Rat Lungworm, Angiostrongylus cantonensis, the Major Cause of Eosinophilic Meningitis - Eamsobhana, Praphathip (University Clinical, Education & Research Associate (UCERA), 2013)
Various aspects of the genetics of the rat lungworm, Angiostrongylus cantonensis, are reviewed. This nematode has an XX/XO sex-determination mechanism, with the female having a 2n = 12 (XX) and the male 2n = 11 (XO) chromosome constitution. Allozymes (12 loci) exhibit a low proportion of polymorphic loci (P = .08) and low mean heterozygosity (H = 0.43) in specimens from Hawai‘i, and no polymorphism or heterozygosity in specimens from Thailand. The phosphoglucomutase-2 (PGM-2) locus exhibits sex-limited expression, with no detectable enzyme activity in the male worms from either location. Based on the 12 allozyme loci, Nei's genetic distance between the Hawai‘i and Thailand isolates is D = 0.03. The p-distance (proportion of nucleotide sites) based on cytochrome c oxidase subunit I (COI) is 3.61% between the Thailand and China isolates as well as between Thailand and Hawai‘i isolates, and 0.83% between China and Hawai‘i isolates. The partial DNA sequences of the 66 kDa protein gene show a great diversity of haplotypes, indicating both inter- and intra-population variation. Intra-specifc sequence variation is also found in the internal transcribed spacer regions. For the small-subunit ribosomal RNA (SSU rRNA) gene, two distinct genotypes have been recorded.